Understanding the Pattern of Sowing-Reaping in Christianity: Efforts to Redesign the Model of Christian Education in Schools Facing the Aftermath of the Covid-19 Pandemic - Divya Baranwal; Jungjungan Simorangkir; Sandy Ariawan (LPPM IAKN Tarutung, 2021)
Pandemic Covid-19 has changed everything, including the education sector. Education is no longer focused on place and time but transforms it from a manual to a virtual space. People have limitations to do activities that can cause crowds. During the Covid-19 pandemic we need to develop an attitude of spirituality that is very useful for children in religious education. Religious education is not a cognitive problem alone but includes emotive and spiritual. Christian educational institutions are expected to develop spiritual approaches that are the future trend of post-pandemic era education. This research aims to provide an overview of the importance of redesigning the model of christian education in school facing the aftermath of the Covid-19 pandemic. This research is a qualitative approach by trying to find the subject and its description by referring to the approach of education experts and can be accounted for scientifically. Therefore, researchers will describe the strategic steps of the spiritual approach education model in the face of the post-Covid 19 or new normal era. From the description can be drawn conclusions about the importance of trying to understand the pattern of sowing-reaping in Christianity. This section needs to get a more share in Christian Education, if the desired result is the formation of a character of learners similar to Christ. Christ's new perspective on the principle of sowing lies in Christ's discernment of the deepest source of the human heart. In this fundamental part lies the entire root of various human deeds. That is why every Christian is called to always live carefully, observantly, critically and prioritize the depth and maturity of his spirituality so that their lives can be constantly illuminated by the Holy Spirit.